2011
DOI: 10.1073/pnas.1012551108
|View full text |Cite
|
Sign up to set email alerts
|

Word lengths are optimized for efficient communication

Abstract: We demonstrate a substantial improvement on one of the most celebrated empirical laws in the study of language, Zipf's 75-y-old theory that word length is primarily determined by frequency of use. In accord with rational theories of communication, we show across 10 languages that average information content is a much better predictor of word length than frequency. This indicates that human lexicons are efficiently structured for communication by taking into account interword statistical dependencies. Lexical s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

27
466
12
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 453 publications
(506 citation statements)
references
References 28 publications
27
466
12
1
Order By: Relevance
“…Our analyses provide evidence that the large majority of directions of metaphorical extensions over history can be explained by a compact set of variables, which suggests that metaphor provides an efficient way of compressing emerging meanings into an existing lexicon, without requiring the construction of word forms de novo. Our work thus extends previous studies about communicative and cognitive constraints on synchronic features of language such as word length (Piantadosi et al, 2011;Zipf, 1949) and semantic structures (Kemp & Regier, 2012;Regier et al, 2015) to explain the evolution of metaphorical polysemy in the lexicon (cf. Blank and Koch, 1999;Geeraerts, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…Our analyses provide evidence that the large majority of directions of metaphorical extensions over history can be explained by a compact set of variables, which suggests that metaphor provides an efficient way of compressing emerging meanings into an existing lexicon, without requiring the construction of word forms de novo. Our work thus extends previous studies about communicative and cognitive constraints on synchronic features of language such as word length (Piantadosi et al, 2011;Zipf, 1949) and semantic structures (Kemp & Regier, 2012;Regier et al, 2015) to explain the evolution of metaphorical polysemy in the lexicon (cf. Blank and Koch, 1999;Geeraerts, 1997).…”
Section: Discussionsupporting
confidence: 82%
“…Piantadosi et al (2011) showed that informativity affects the length (in segments) of words in the lexicons of several European languages, and Seyfarth (2014) found that informativity affects word duration. Adams et al (2009) found that informativity affects the duration and deletion ratios of German codas.…”
Section: Discussionmentioning
confidence: 99%
“…Informativity has been shown to affect both duration and deletion (Cohen Priva 2008;Cohen Priva and Jurafsky 2008;Adams et al 2009), word-length (measured in segments; Piantadosi et al 2011), and word duration, after word predictability and phonological structure have been controlled for (Seyfarth 2014).…”
Section: Informativitymentioning
confidence: 99%
See 1 more Smart Citation
“…For information-theoretic approaches to language production in particular, the empirical base is further limited, since this work tends to require larger databases on the basis of which informativity can be estimated (Bell, Brenier, Gregory, Girand, & Jurafsky, 2009 ;Piantadosi et al, 2011 ;Resnik, 1996 ). To the extent that cross-linguistic investigations within information-theoretic frameworks exist, they have thus mostly focused on lexical and sublexical properties, i.e., levels of linguistic description for which units are more frequent (e.g., Graff & Jaeger, 2009;Pellegrino, Coupé, & Marsico, 2011 ;Piantadosi et al, 2011 ;Qian & Jaeger, 2012 ;Wedel et al, 2013 ). Above the lexical level, some suggestive cross-linguistic support for communicative effi ciency in fact comes from the comprehension research fi nding that comprehenders e x pe c t speakers to produce reduced forms when the meaning the form conveys is contextually expected, and less reduced forms otherwise.…”
Section: Introductionmentioning
confidence: 99%